Determination of nitrofurantoin and fosfomycin susceptibility among urinary Escherichia coli isolates - Kanaujia, Rachana; Kumar, Amit; Bajpai, Malay (International Journal of Research in Medical Sciences, 2020)
Background: Urinary tract infections (UTIs) are one of the most common infections. For treatment of UTIs, there are limited antibiotics due to increased resistance among uropathogens. Two older antibiotics; Nitrofurantoin and Fosfomycin have become novel oral therapeutic options against uropathogens. Aim of the study was to identify UTI causing micro-organisms and evaluate in-vitro activity of nitrofurantoin and fosfomycin against most common isolated organism (E. coli). Methods: Results of urine samples culture and susceptibility testing over a period of 1 year were analysed and included in this study. Results: Micro-organisms were isolated from 568 urine samples. Most commonly isolated organism was Escherichia coli (40.50%), followed by Klebsiella spp. (20.07%) and Staphylococcus spp. (17.07%). Susceptibility of E. coli to nitrofurantoin and fosfomycin was 91.74% and 65.65% respectively. Conclusion: Good activity of nitrofurantoin and fosfomycin against E. coli indicates that these two drugs are potential therapeutic alternatives for urinary tract infections.